2019
DOI: 10.1108/ec-04-2018-0169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gap influence on the dynamic response behavior of pump-turbine runner

Abstract: Purpose The gaps between runner and nearby structures play an important role in the dynamic response of runner, especially for pump-turbines. This paper aims to evaluate the gap influence on the added mass and dynamic stress of pump-turbine runner and provide an improved method to predict the resonance of runner. Design/methodology/approach Acoustic-structural coupling method was used to evaluate the added mass factors of a reduced scale pump-turbine with different axial and radial gap size between runner an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In traditional FSI simulation, only loads on inner surface are considered. However, the loads on outer surface also have a great influence on the stress-state of runner [25] and were considered in this paper.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…In traditional FSI simulation, only loads on inner surface are considered. However, the loads on outer surface also have a great influence on the stress-state of runner [25] and were considered in this paper.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The fixed constraints were set on the shaft-connecting The geometry of the runner is much more complicated than that of the disk. Therefore, there are some special vibration patterns in ND and NC modes, such as crown dominant (CD), band dominant (BD), and counter phase (CP) [15]. In addition, the modes of the runner also include the vibration modes dominated by blades.…”
Section: Modes Under Different Constraintsmentioning
confidence: 99%
“…Additionally, the smaller the thickness, the more significant the influence. Similarly, He et al [15] studied the effect of the clearance on the dynamic characteristics of a pump turbine runner using the acoustic-structure coupling method. The results showed that the thickness of the clearance between the runner and the wall has a significant impact on the resonance condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some researchers have tried to simplify the N-S equation; a widely used method is the acoustic fluid-structural coupling method [6]. He et al investigated the modal characteristics and the dynamic response characteristics of a pump-turbine runner and discussed the added mass effect in detail [7]. Lais characteristics of a Francis turbine runner on the basis of the acoustic fluid-structural coupling method [8], and the numerical method was verified by the experimental results.…”
Section: Introductionmentioning
confidence: 99%